Інтерференційна частина синхротронного випромінювання - Яремко, Ю. (Праці наукового товариства ім. Шевченка, 2011)
Energy-momentum and angular momentum carried by electromagnetic field of two point-like charged particles arbitrarily moving in at spacetime are presented. Apart from usual contributions to the Noether quantities produced separately by particle 1 and particle 2 the conservation laws also contain a joint contribution due to the fields of both particles. The mixed part of Maxwell energy-momentum density is decomposed into bound and radiative components which are separately conserved off the world lines of particles. The former describes the deformation of electromagnetic clouds of “bare” charges due to mutual interaction while the latter defines the radiation which escapes to infinity The bound terms contribute to individual 4-momenta of particles while the radiative ones exert the radiation reaction. The analysis of energy-momentum and angular momentum balance equations results in the Lorentz-Dirac equation as an equation of motion for a pointed charge under the effect of its own electromagnetic field as well as of the field produced by another charge.